Voltammetric determination of biogenic amines on the electrodes of carbon nanotubes modified with polyaniline - Zagorovskiy, G. M.; Sydorenko, I. G.; Vlasova, N. M.; Lobanov, V. V. (Chuiko Institute of Surface Chemistry National Academy of Sciences of Ukraine, 2008)
In order to raise sensitivity of cyclic voltammetry method for determination of biogenic amines in aqueous solution, paste electrodes of carbon nanotubes modified with polyaniline films were use. Utilization of those electrodes for determination of phenylethylamine and tyramine concentration in water gives a possibility to increate sensitivity of the method almost to order of magnitude.